Relationship between Risk and Return: Evidence from Dow Jones Sukuk Price Index - Rauf, Ahamed Lebbe Abdul (Eastern Journal of Economics and Finance, 2016)
The objectives of this study are to identify the different types of risk embedded in the sukuk structure and to find the relationship between the identified risks and the returns of sukuk among dow jones sukuk price index. Data were collected from 2005 to 2015 on a periodic monthly basis and analyzed using descriptive, correlation analysis and multi-regressions analysis. Dow Jones (DJ) price sukuk return is exposed 90% to risk. F statistics shown that the models are significant at the 5% level and all models are acceptable. Findings confirmed that the regression model based on Dow Jones price sukuk return is slightly higher exposed to risk in the sukuk structure. For DJ price sukuk returns, while the DOR has a negative relationship with return IRD, CPI, CCI, MPR, SMB, HQR, RIR and have positive relationships. Of these positive relationships, CPI has the highest positive relationship. Contrarily, RIR has the least positive relationship. According to the results, impact of IRD and CPI are significant at the 1% level, and other all risks in this category are significant at the 5% level. Results confirmed the significant influence of market risk, credit risk, operational risk and liquidity risk on the sukuk returns in different ways. Findings of this study recommend to maintain inflation- rate risk at an optimal level, hedging their interest- rate risk with Libor, and taking necessary measures to provide a conducive environment to promote secondary markets for sukuk.